Integration of Entrepreneurship in High School Curriculum: Opportunities and Challenges - Herlina Herlina; Romansyah Sahabuddin; Bustan Bustan (Departement of Mathematics Education, 2024)
This study highlights the importance of integrating entrepreneurship into the high school curriculum in Indonesia to prepare students for the increasingly complex challenges of the workforce. Integrating entrepreneurship into the curriculum offers significant opportunities, such as enhancing 21st-century skills, fostering collaboration with the business sector, and enabling students to create economic opportunities through independent ventures. However, its implementation faces various challenges, including limited resources, time constraints, and insufficient teacher competencies. The study adopts a descriptive qualitative approach, analyzing existing education policies and findings from interviews with teachers and practitioners of entrepreneurship education. The results emphasize the need for policies that support the integration of entrepreneurship into the national education curriculum and allocate resources for teacher training to enhance the quality and effectiveness of entrepreneurship education.